PENGEMBANGAN MODEL PEMBERDAYAAN PENYANDANG CACAT FISIK (PEOPLE WITH DISABILITY) DI BIDANG PARIWISATA - Rara Sugiarti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2007)
The aims ofthis research are 10 identify the empirical conditions of tourism job opportunities involving people with disability in the SUBOSUKA WONOSRATEN (Kota Surakarta, Kabupaten Boyolali, Sukoharjo, Karanganyar, Wonogiri, Sragen dan Klaten) region, identify tourism stake· holder perception on people with disability in the tourism industry, and to formulate a model of empowering people with disability as human resources in the tourism industry, This research was qualitative in nature. Data were collected using site observation. interview and document study. Results indicate that there is still a limited number of people with disability who work in the tourism industry, This is among others due to the lack ofcommitment and awareness of tourism stakeholders towards people with disability.